2017
DOI: 10.1021/acs.biochem.7b00584
|View full text |Cite
|
Sign up to set email alerts
|

Human CST Prefers G-Rich but Not Necessarily Telomeric Sequences

Abstract: The human CST (CTC1–STN1–TEN1) heterotrimeric complex plays roles in both telomere maintenance and DNA replication through its ability to interact with single-stranded DNA (ssDNA) of a variety of sequences. The precise sequence specificity required to execute these functions is unknown. Telomere-binding proteins have been shown to specifically recognize key telomeric sequence motifs within ssDNA while accommodating nonspecifically recognized sequences through conformationally plastic interfaces. To better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…Specificity for chromosome ends is mediated by a high affinity DNA binding domain in Cdc13, which exhibits exceptional sequence preference for single-stranded G-rich telomeric sequences in budding yeast (19) and closely related species (20), leading us to refer to it as a t-RPA complex. This contrasts with the genome-wide role performed by this conserved RPA-like complex in multiple other species (21)(22)(23)(24), consistent with the lack of strong specificity for telomeric DNA (25).…”
Section: Introductionmentioning
confidence: 72%
“…Specificity for chromosome ends is mediated by a high affinity DNA binding domain in Cdc13, which exhibits exceptional sequence preference for single-stranded G-rich telomeric sequences in budding yeast (19) and closely related species (20), leading us to refer to it as a t-RPA complex. This contrasts with the genome-wide role performed by this conserved RPA-like complex in multiple other species (21)(22)(23)(24), consistent with the lack of strong specificity for telomeric DNA (25).…”
Section: Introductionmentioning
confidence: 72%
“…6). Given that CST prefers binding to DNA with specific sequence (G-rich repetitive) and structural features (ss-ds junctions) (Bhattacharjee et al, 2017;Chastain et al, 2016;Hom & Wuttke, 2017) while BRCA2 binds to G-rich oligos with low affinity (Yang et al, 2002), it is possible that CST may be a surrogate of BRCA2 that is particularly important for maintaining the stability of G-rich repetitive sequences and/or sequences prone to form special structures -an interesting hypothesis to be further tested. Alternatively, it remains a possibility that CST and BRCA2 may occupy the same stalled site at different time following fork stalling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CST prefers binding to DNA with G-rich repetitive sequences and structural features including ss-ds junctions (Bhattacharjee et al, 2017;Chastain et al, 2016;Hom & Wuttke, 2017). We postulated that CST might localize at forks stalled at non-BRCA2 binding regions and be particularly important for protecting the stabilities of these sequences.…”
Section: Spatial Relationship Between Cst and Brca2mentioning
confidence: 94%
See 1 more Smart Citation
“…Although CST and RPA share many similarities in terms of structure and DNA binding activity, they are architecturally different and they play quite distinct roles during DNA replication and repair [26]. Moreover, CST binds preferentially to G-rich ssDNA and, unlike ssDNA-bound RPA, it does not trigger ATR activation [19,25,27].…”
Section: Introductionmentioning
confidence: 99%